2020
DOI: 10.17977/um017v25i22020p161
|View full text |Cite
|
Sign up to set email alerts
|

Environmental awareness and pro-environmental behavior: A case of university students in Malang city

Abstract: University students exhibit low commitment towards pro-environmental behavior despite the facts that they know a lot about environmental issues. The objective of this study was (1) to know the level of environmental awareness and pro-environmental behavior and (2) to find relationship between environmental awareness and pro-environmental behavior among university students in Malang city. This study used descriptive quantitative research design using survey method. Data were collected using questionnaire instru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
22
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 0 publications
3
22
0
2
Order By: Relevance
“…One was to help them better understand pro-environmental and environment-unfriendly behaviors of visitors. Pro-environmental behaviors are behaviors that an individual does to reduce environmental destruction and to conserve the environment [5], and environmentally unfriendly behaviors are the behaviors detrimental to the environment. In the survey task, students discovered environmentally unfriendly behaviors visitors performed in the parks.…”
Section: Content Design Of the Project Modulesmentioning
confidence: 99%
See 1 more Smart Citation
“…One was to help them better understand pro-environmental and environment-unfriendly behaviors of visitors. Pro-environmental behaviors are behaviors that an individual does to reduce environmental destruction and to conserve the environment [5], and environmentally unfriendly behaviors are the behaviors detrimental to the environment. In the survey task, students discovered environmentally unfriendly behaviors visitors performed in the parks.…”
Section: Content Design Of the Project Modulesmentioning
confidence: 99%
“…Pro-environmental awareness is the awareness of environmental issues and measures to be taken to bring about good practices towards environment conservation [5]. It is the main driving factor of pro-environmental behaviors [6].…”
Section: Introductionmentioning
confidence: 99%
“…Finally, the present study believes that educational institutions, i.e., colleges or universities, play an essential role in creating awareness among their students about different ecological issues, which resultantly provokes the students to show eco-protective behaviors that is beneficial for environmental quality. However, to the best of our knowledge, only a few researchers have examined the role of environmental awareness and climate change awareness among university students [16].…”
Section: Empirical Gap/contributions Of the Studymentioning
confidence: 99%
“…They indicated that educational institutions, i.e. ; colleges or universities, play a critical role in promoting environmental awareness (EA), knowledge, and education among their students to promote their eco-friendly behaviors [15,16], which, in turn, limit environmental problems.…”
Section: Introductionmentioning
confidence: 99%
“…This Eco literation can be embedded in an individual into beliefs, idealism, character, and the ability to manage and care for nature only if through a process of habituation, it occurs throughout his life (Kurniasari et al, 2020). Environmental awareness is a form of mindset created by behavior and interactions with the environment in order to maintain the balance of the ecological world (Mkumbachi, et al, 2020). Eco literation is able to direct humans to be able to live side by side with nature with the habituation of a lifestyle that loves the universe which will then develop into a culture that develops in society and then has a major impact on global life (Rusmana & Akbar, 2017;Maurer et al, 2020).…”
Section: Introductionmentioning
confidence: 99%